Trust, openness and continuity of care influence acceptance of antibiotics for children with respiratory tract infections: a four country qualitative study. - Brookes-Howell, L; Wood, F; Verheij, T; Prout, H; Cooper, L; Hood, K; Melbye, H; Torres, A; Godycki-Cwirko, M; Fernandez-Vandellos, P; Ystgaard, M; Falk Taksdal, T; et al. (2014)
BACKGROUND: Clinician-parent interaction and health system influences on parental acceptance of prescribing decisions for children with respiratory tract infections (RTIs) may be important determinants of antibiotic use. OBJECTIVE: To achieve a deeper understanding of parents' acceptance, or otherwise, of clinicians' antibiotic prescribing decisions for children with RTIs. METHODS: Qualitative interviews with parents of child patients who had recently consulted in primary care with a RTI in four European countries, with a five-stage analytic framework approach (familiarization, developing a thematic framework from interview questions and emerging themes, indexing, charting and interpretation). RESULTS: Fifty of 63 parents accepted clinicians' management decisions, irrespective of antibiotic prescription. There were no notable differences between networks. Parents ascribed their acceptance to a trusting and open clinician-patient relationship, enhanced through continuity of care, in which parents felt able to express their views. There was a lack of congruence about antibiotics between parents and clinicians in 13 instances, mostly when parents disagreed about clinicians' decision to prescribe (10 accounts) rather than objecting to withholding antibiotics (three accounts). All but one parent adhered to the prescribing decision, although some modified how the antibiotic was administered. CONCLUSIONS: Parents from contrasting countries indicated that continuity of care, open communication in consultations and clinician-patient trust was important in acceptance of management of RTI in their children and in motivating adherence. Interventions to promote appropriate antibiotic use in children should consider a focus on eliciting parents' perspectives and promoting and building on continuity of care within a trusting clinician-patient relationship.